2018
DOI: 10.1038/s41593-018-0090-8
|View full text |Cite|
|
Sign up to set email alerts
|

Repopulated microglia are solely derived from the proliferation of residual microglia after acute depletion

Abstract: Newborn microglia rapidly replenish the whole brain after selective elimination of most microglia (>99%) in adult mice. Previous studies reported that repopulated microglia were largely derived from microglial progenitor cells expressing nestin in the brain. However, the origin of these repopulated microglia has been hotly debated. In this study, we investigated the origin of repopulated microglia by a series of fate-mapping approaches. We first excluded the blood origin of repopulated microglia via parabiosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
398
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 440 publications
(487 citation statements)
references
References 41 publications
45
398
3
1
Order By: Relevance
“…Here, we show that repopulated microglia display high expression of both TMEM119 and P2RY12 (Figure 2k–n), demonstrating that repopulated microglia are indeed resident microglia and do not originate from peripherally‐derived myeloid cells. These findings are in line with previous studies from our laboratory (Elmore et al, 2014) and others (Cronk et al, 2018; Huang et al, 2018) showing that repopulating microglia are CNS‐derived and not from peripheral infiltrates. Thus, CSF1R inhibitor‐directed replacement of microglia in the aged brain restores age‐induced changes in microglial numbers, morphologies, and CD68 puncta, reverting the microglial phenotype to that observed in the young brain, at least out to 28 days.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we show that repopulated microglia display high expression of both TMEM119 and P2RY12 (Figure 2k–n), demonstrating that repopulated microglia are indeed resident microglia and do not originate from peripherally‐derived myeloid cells. These findings are in line with previous studies from our laboratory (Elmore et al, 2014) and others (Cronk et al, 2018; Huang et al, 2018) showing that repopulating microglia are CNS‐derived and not from peripheral infiltrates. Thus, CSF1R inhibitor‐directed replacement of microglia in the aged brain restores age‐induced changes in microglial numbers, morphologies, and CD68 puncta, reverting the microglial phenotype to that observed in the young brain, at least out to 28 days.…”
Section: Resultssupporting
confidence: 92%
“…Measurements of the chow‐administered PLX5622 in both plasma and brain tissue revealed a comparable reduction in inhibitor levels in aged mice, reflecting either reduced chow‐intake with aging, an increased metabolism and excretion of the compound, or an altered sensitivity of microglia with age. Recent data indicate that repopulating microglia with PLX5622 mainly derive from proliferation of surviving microglia (Huang et al, 2018), suggesting that regardless of the comparative extent of microglial depletion, the source of the resultant tissue is the same. Moreover, cell proliferation can reset (Bufalino & van der Kooy, 2014; Unruh, Slaughter, & Li, 2013) and rejuvenate (Chishti et al, 2013; Pattabiraman & Kaganovich, 2014) cellular phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bruttger et al demonstrated that following partial depletion (80%) in the CX3CR1 CreER iDTR mouse, microglia proliferate by themselves rather than from nestin + microglial progenitor cells to finally refill the niche (Figure d) (Bruttger et al, ; Jakel & Dimou, ). This mechanism has received further support (Askew et al, ) including using elegant fate‐mapping approaches, single‐cell RNA sequencing and parabiosis (Huang, Xu, Xiong, Sun, et al, ).…”
Section: Microglial Repopulation Resolves Neuroinflammation: New Cellmentioning
confidence: 99%
“…Maturation and development of microglia requires colony stimulating factor‐1 receptor (CSF1R) Ginhoux et al, ) and the transcription factors Pu.1 and Irf8 (Kierdorf et al, ). The existence of a microglia progenitor cell (Elmore et al, ) versus proliferation of existing or residual microglia (depending on experimental context; Huang et al, ) is an ongoing debate. However, it is clear from multiple studies that microglia proliferate in response to injury (Tay et al, ) including prolonged cerebral ischemia (Denes et al, ; Moraga et al, ).…”
Section: Introductionmentioning
confidence: 99%